1979
DOI: 10.1161/01.res.44.6.767
|View full text |Cite
|
Sign up to set email alerts
|

The role of potassium in the metabolic control of coronary vascular resistance of the dog.

Abstract: We tested the hypothesis that potassium ion (K+) is involved in the local control of the coronary circulation. The left coronary artery was perfused at constant flow in closed-chest, anesthetized dogs. Step increases in heart rate caused transient (six dogs) or sustained (three dogs) increases in coronary sinus plasma [K+] averaging 0.53 mEq/liter. When the effects of vascular transit delay were accounted for, we found that [K+] changes preceded the vasodilation seen with increased heart rate. We used a mathem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…In this study, K ϩ -mediated vasodilation occurred through both inwardly rectifying K ϩ (K IR ) channels and Na ϩ -K ϩ -ATPase, similar to the mechanisms of K ϩ -mediated vasodilation in humans (17,21). Furthermore, these animal data substantiated early observations showing that changes in interstitial K ϩ concentration after brief muscle contraction have the appropriate magnitude and time course to have a significant involvement in the hyperemic response (26,35,39,50,53,54) and that smooth muscle vascular hyperpolarization may be essential to observe rapid vasodilation (33). Whether K ϩ -mediated vasodilation contributes to contraction-induced rapid vasodilation in humans is unknown.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…In this study, K ϩ -mediated vasodilation occurred through both inwardly rectifying K ϩ (K IR ) channels and Na ϩ -K ϩ -ATPase, similar to the mechanisms of K ϩ -mediated vasodilation in humans (17,21). Furthermore, these animal data substantiated early observations showing that changes in interstitial K ϩ concentration after brief muscle contraction have the appropriate magnitude and time course to have a significant involvement in the hyperemic response (26,35,39,50,53,54) and that smooth muscle vascular hyperpolarization may be essential to observe rapid vasodilation (33). Whether K ϩ -mediated vasodilation contributes to contraction-induced rapid vasodilation in humans is unknown.…”
supporting
confidence: 84%
“…Unfortunately, in our human forearm model, we were not able to inhibit K ϩ efflux from contracting muscle, and thus we are limited in the conclusions we are able to make regarding the source of K ϩ , as it could derive from skeletal muscle, as suggested by Armstrong and colleagues, or alternatively from small-and intermediate-conductance Ca 2ϩ -activated K ϩ channels on endothelial cells (28). K ϩ is an attractive candidate for the stimulus of rapid vasodilation as the time course is appropriate, it causes hyperpolarization via stimulation of both K IR and Na ϩ -K ϩ -ATPase, and, if originating from contracting skeletal muscle, would serve as a feedforward mechanism that couples rapid vasomotor responses with muscle activation (9,22,53). Additionally, an animal study (9) has reported that K ϩ -mediated vasodilation is most often transient in nature, and this may in part contribute to the distinct temporal pattern of the response.…”
Section: Potential Stimuli For Vasodilation After a Single Muscle Conmentioning
confidence: 99%
“…5 This is in agreement with our present finding in porcine coronary subepicardial arterioles that KCl-induced dilation is sensitive to Ba 2ϩ . Interestingly, the K ϩ -induced vasodilation has been suggested to be one of the mechanisms involved in the metabolic regulation of coronary blood flow because the increased K ϩ concentration during metabolic activation 10 or stress 11 is sufficient to evoke coronary vasodilation.…”
Section: Discussionmentioning
confidence: 99%
“…26 Interstitial volume variations are to be expected with changes in flow, both in control and with adenosine, by variation of capillary pressure 27 but also with saline infusion by decreasing plasma oncotic pressure. Also, the time course of DTF variation, being slower than intravascular volume variations, 28 is consistent with this hypothesis.…”
Section: Possible Mechanisms Of Increasing Dtfmentioning
confidence: 99%